HYPHa project: a low-cost alternative for integrated photonics - Butt, Muhammad Ali; Kaźmierczak, Andrzej; Tyszkiewicz, Cuma; Karasiński, Paweł; Środa, Edyta; Olszewski, Jacek; Pala, Piotr; Martynkien, Tadeusz; Hlushchenko, Daria; Baraniecki, Tomasz; Bachmatiuk, Alicja; Jusza, Anna; et al. (Photonics Letters of Poland, 2022)
In this paper, a brief introduction to the Hybrid sensor platforms of integrated photonic systems based on ceramic and polymer materials (HYPHa) is presented. The project's goal is to establish a collaborative effort of institutes specialized in integrated optics. The newly formed group of professionals will be founded on research groups' experience, collaboration, and devotion. We intend to develop a method for combining competencies and a universal material platform for integrated photonics, based on newly validated hybrid materials as part of the project. Silica compounds with additions including TiO2, SnO2, used as structural matrices, polymer coatings with dopants (active or protective layers), organic dyes, and active two-dimensional materials such as transition metal dichalcogenides, graphene hybrids, and boron nitride will be the foundation for these materials. Full Text: PDF References K. Rola, A. Zajac, M. Czajkowski, A. Szpecht, M. Zdonczyk, M. Smiglak, J. Cybinska, K. Komorowska, "Ionic liquids for active photonics components fabrication", Opt. Mater. 89, 106-111 (2019). CrossRef D. Kowal, K. Rola, J. Cybinska, M. Skorenski, A. Zajac, A. Szpecht, M. Smiglak, S. Drobczynski, K. Ciesiolkiewicz, K. Komorowska, "Fluorescent ionic liquid micro reservoirs fabricated by dual-step E-beam patterning", Mater. Res. Bull. 142, 111434 (2021). CrossRef T. Martynkien, J. Olszewski, M. Szpulak, G. Golojuch, W. Urbanczyk, T. Nasilowski, F. Berghmans, and H. Thienpont, "Experimental investigations of bending loss oscillations in large mode area photonic crystal fibers", Opt. Express 15, 13547-13556 (2007). CrossRef E. Środa, J. Olszewski, and W. Urbańczyk, "Reducing bend-induced loss and crosstalk in a two-mode ridge waveguide by steplike thickness structuring", Appl. Opt. 61, 1164-1170 (2022). CrossRef P. Karasinski, C. Tyszkiewicz, A. Domanowska, A. Michalewicz, J. Mazur, "Low loss, long time stable sol–gel derived silica–titania waveguide films", Mater. Lett. 143, 5-7 (2015). CrossRef P. Karasinski, C. Tyszkiewicz, A. Maciaga, I.V. Kityk, E. Gondek, "Two-component waveguide SiO2:TiO2 films fabricated by sol–gel technology for optoelectronic applications", J. of Mater. Sci.: Mater. Electron. 26, 2733-2736 (2015). CrossRef M.A. Butt, A. Kazmierczak, C. Tyszkiewicz, P. Karasinski, R. Piramidowicz, "Mode Sensitivity Exploration of Silica–Titania Waveguide for Refractive Index Sensing Applications", Sensors 21, 7452 (2021). CrossRef A. Kazmierczak, M. Slowikowski, K. Pavlov, M. Filipiak, M. Vervaeke, C. Tyszkiewicz, H. Ottevaere, R. Piramidowicz, P. Karasinski, "Efficient, low-cost optical coupling mechanism for TiO2-SiO2 sol-gel derived slab waveguide surface grating coupler sensors", Opt. Appl. 50, 539 (2020). CrossRef M.A. Butt, S.N. Khonina, N.L. Kazanskiy, "A highly sensitive design of subwavelength grating double-slot waveguide microring resonator", Laser Phys. Lett. 17, 076201 (2020). CrossRef N.L. Kazanskiy, M.A. Butt, S.N. Khonina, "Silicon photonic devices realized on refractive index engineered subwavelength grating waveguides-A review", Opt. Laser Technol. 138, 106863 (2021). CrossRef M.A. Butt, S.N. Khonina, N.L. Kazanskiy, "Recent advances in photonic crystal optical devices: A review", Opt. Laser Technol. 142, 107265 (2021). CrossRef L. Xu, Y. Wang, E. El-Fiky, D. Mao, A. Kumar, Z. Xing, Md. G. Saber, M. Jacques, D.V. Plant, "Compact Broadband Polarization Beam Splitter Based on Multimode Interference Coupler With Internal Photonic Crystal for the SOI Platform", J. Light. Technol. 37, 1231 (2019). CrossRef R. Marchetti, C. Lacava, A. Khokhar, X. Chen, I. Cristiani, D.J. Richardson, G. T. Reed, P. Petropoulos, P. Minzioni, "High-efficiency grating-couplers: demonstration of a new design strategy", Sci. Rep. 7, 16670 (2017). CrossRef